2018
DOI: 10.20319/pijss.2018.42.466476
|View full text |Cite
|
Sign up to set email alerts
|

Where Are We? Lecturers Receptivity of Service Learning in Nigeria

Abstract: Universities in Nigeria are established to perform three functions-teaching, research and community service. In spite of the establishment of several government and private-owned universities in Nigeria, most of these tertiary institutions have been criticised for not meeting the objectives of their establishment. This is because gaps between the gown and the town exist to the extent that the functionality of the education provided and the relevance of the certificates awarded to the society are being question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Recent studies showed public universities in Nigeria like their counterparts in other parts of the world have adopted the use of experiential learning methods in replacement of the traditional method of teaching and learning often referred to as the storytelling methods (Gbadamosi, 2018). Experiential form of learning involves students actively participating in the learning process, it entails the immediate hands-on experience of what is being taught in the classroom for learning.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed public universities in Nigeria like their counterparts in other parts of the world have adopted the use of experiential learning methods in replacement of the traditional method of teaching and learning often referred to as the storytelling methods (Gbadamosi, 2018). Experiential form of learning involves students actively participating in the learning process, it entails the immediate hands-on experience of what is being taught in the classroom for learning.…”
Section: Introductionmentioning
confidence: 99%
“…Studies proved that servicelearning as a form of pedagogy improves students' academic performance as students construct new knowledge from their experiences and the ability to relate their experience with the theoretical knowledge obtained in the classroom through reflection (Brondani, 2012). The Studies show the form of pedagogy to train students to think critically and effectively solve societal challenges such as hunger, poverty, and redundancy, among others (Dugguh, 2018;. To this effect, service-learning as an experiential study is gradually taking its roots in the tertiary education system of Nigeria for the effective development of students who can handle next-generation challenges (Deba, Jabor, Buntat, & Musta'mal, 2014).…”
mentioning
confidence: 99%